Studi Mad’u dan Teori Resepsi Stuart Hall: Analisis Komentar Netizen pada Ceramah Virtual Buya Yahya - Hakim, Lukman; Dwi Magfiroh, Ervina Putri (Jurnal Komunikasi Islam, 2024)
This article reports on the textual thematic research conducted with 100 Netizens' comments on the YouTube channel of Al-Bahjah TV entitled "Tanggapan Buya Yahya tentang Fatwa MUI Haram Membeli Produk Isra*l/Yahudi (The Response of Buya Yahya to the MUI Fatwa on the Prohibition of Buying Israeli/Jewish Products)”. This study uses thematic analysis and Stuart Hall's reception theoretical framework to examine Netizens' (mad’u) reception towards Buya Yahya's online preaching regarding MUI recommendation for Muslims to avoid buying any products affiliated with Israel. The findings illustrate three different mad'u receptions, namely dominant hegemonic reading (48), negotiated reading (22), and oppositional reading (30). The Netizens' (mad'u) cultural background influenced the variety of their reading positions of Buya Yahya's preaching, which resulted in several different types of arguments: humanity, religion, economy, socio-politics, and commodification of religion.